Optimizing budget allocation among project activities - Golenko‐Ginzburg, Dimitri; Laslo, Zohar; Ben‐Yair, Avner; Baron, Anna (Journal of Business Economics and Management, 2006)
The problems of optimal budget allocation among project's activities are considered. The formulated optimization models and their solution can be used in planning, as well as in control and monitoring of individual projects in modern design offices. Models of budget allocation for PERT‐COST type networks, are considered as well. The problem is to schedule a realization of all project's activities in order to accomplish the project on time, i.e., not later than the given due date, with minimal expenses, taking into account limitations on dynamics of resources consumption during the scheduled period. The solution is based on decomposition principle, i.e., decomposing a network project into network fragments, replacing them by a small number of aggregated activities, solving the problem for aggregated network project, and disaggregating the network diagram in order to schedule each project's activity.First published online: 14 Oct 2010